2023
DOI: 10.3389/fimmu.2022.1067950
|View full text |Cite
|
Sign up to set email alerts
|

The role of intestinal immune cells and matrix metalloproteinases in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) has become globally intractable. MMPs play a key role in many inflammatory diseases. However, little is known about the role of MMPs in IBD. In this study, IBD expression profiles were screened from public Gene Expression Omnibus datasets. Functional enrichment analysis revealed that IBD-related specific functions were associated with immune pathways. Five MMPS-related disease markers, namely MMP-9, CD160, PTGDS, SLC26A8, and TLR5, were selected by machine learning and the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…KNEP eased acute enteritis in DSS‐induced IBD mice in a dose‐dependent manner (Lang‐Schwarz et al., 2021). We also found that the colon tissue of mice with acute enteritis was devoid of mucosa, the crypts contained several neutrophils, the structure was incomplete, and the inflammatory cell infiltration was severe (Mei et al., 2023). KNEP improved anti‐inflammatory activity in colon, inhibited the expression of inflammatory factors, promoted repair of the damage to the intestinal flora structure caused by IBD, and improved and protected the intestinal structure stimulated by DSS in mice.…”
Section: Discussionmentioning
confidence: 91%
“…KNEP eased acute enteritis in DSS‐induced IBD mice in a dose‐dependent manner (Lang‐Schwarz et al., 2021). We also found that the colon tissue of mice with acute enteritis was devoid of mucosa, the crypts contained several neutrophils, the structure was incomplete, and the inflammatory cell infiltration was severe (Mei et al., 2023). KNEP improved anti‐inflammatory activity in colon, inhibited the expression of inflammatory factors, promoted repair of the damage to the intestinal flora structure caused by IBD, and improved and protected the intestinal structure stimulated by DSS in mice.…”
Section: Discussionmentioning
confidence: 91%
“…GERD occurs when stomach contents flow back into the esophagus due to attenuated esophageal clearance and antireflux barrier mechanisms. The resulting mucosal injury is a result of both direct damage from gastric juice and an immune and inflammatory response, wherein inflammatory cytokines released by the esophageal mucosal epithelium induce neutrophil migration, leading to inflammation [23]. The onset and progression of GERD are multifaceted.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are involved in several types of diseases and generally related to three main mechanisms: tissue destruction, such as cancer (e.g., acute myeloid leukemia and bladder, brain, breast, colorectal, endometrial, gastric, head and neck, liver, lung, ovarian, pancreas, prostate, renal, skin, and thyroid cancer), diabetes, inflammatory diseases (e.g., psoriasis, osteoarthritis, rheumatoid arthritis, inflammatory bowel disease), chronic wounds (e.g., pressure ulcers, vascular ulcers), periodontal diseases, hypertension, kidney diseases (e.g., chronic kidney disease, glomerular disease), myocardial infarction, and neurogenerative disease (e.g., multiple sclerosis, Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis); fibrosis, such as liver cirrhosis, otosclerosis, gynecological disorders (e.g., polycystic ovarian syndrome, spontaneous abortion, preeclampsia), and atherosclerosis-related diseases; and weakening of the ECM, such as chronic venous disease, pulmonary embolism, aneurysms, and dilated cardiomyopathy. Often, more than one mechanism overlaps in determining the disease [2,3,7,11,19,22,[37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: The Matrix Metalloproteinase (Mmp) Familymentioning
confidence: 99%